Drug survival of methotrexate and predictor factors for discontinuation in psoriasis. (24th March 2023) - Caldarola, Giacomo; De Luca, Eleonora; Mariani, Marco; Chiricozzi, Andrea; Peris, Ketty; De Simone, Clara
Abstract: Background: Methotrexate (MTX) is a systemic therapy largely used for moderate‐severe psoriasis. There is a lack of data on its use in daily practice and particularly on its long‐term effectiveness and survival in psoriasis. Methods: We performed a single‐centered, retrospective, observational study to evaluate the drug survival of MTX in patients with psoriasis, treated in monotherapy with MTX between March 2015 and March 2022. Clinical and demographic characteristics were extracted from files of the patients. The drug survival was analyzed using Kaplan‐Meier survival curves, considering separately overall discontinuation, discontinuation due to MTX ineffectiveness, and discontinuation due to adverse events. Multivariable Cox regression analyses were carried out including clinically meaningful variables. Results: A total of 199 patients were included; 148 (74.4%) suspended MTX during the observation period. The reasons for discontinuation were adverse events (39.2%), ineffectiveness (38.5%), remission of psoriasis (12.2%), and other reasons (10.1%). Average duration of therapy was 10.1 months. Patients who remained on therapy after 1, 2, and 5 years of treatment were respectively 46.9, 35.6, and 29.3%. Positive predictive factors for therapy continuation were increasing age and the use of >15 mg of MTX for a period >3 months; the only negative predictive factor was the clinical variant of palmoplantar pustular. Conclusions: MTX is a valuable, cost‐effective option for long‐term treatment of psoriasis although drug survival is not comparable with that of biological treatments. Studies are needed to better understand the best dosing regimen to use, with the aim of achieving the best clinical outcomes and the lowest rate of side effects with this drug.